PROBLEMS AND PRIORITIES OF THE DEVELOPMENT OF THE TOURIST COMPLEX OF UKRAINE (Development Service Industry Management, 2024)
The article focuses on the potential of tourism development in Ukraine. Problematic aspects and obstacles to the formation and effective functioning of the tourist complex of the country and its regions are indicated. Based on these principles, the purpose of the study is to identify problematic aspects and justify the priority directions of the state policy for the development of the tourist complex of Ukraine. The directions and instruments of the state policy of stimulating the processes of building tourist complexes as systems have been determined. Mechanisms and means of state regulation have been identified, the implementation of which will allow to increase the volume of tourist services, increase tourist flows and increase the share of tourism in GDP, accelerate local economic and social development due to tourism, and improve the quality of life of the local population. It is shown that the state policy in the field of tourism should be built on the basis of the consolidation of all interested forces in different forms, under different conditions and with different goals. Based on the analysis, it was determined that the principles of modern tourism policy of Ukraine should be decentralization, delegation of powers to local self-government bodies, support of local initiatives, development of all forms of social tourism, the principle of comprehensive cooperation between the authorities, territorial communities and entrepreneurs in the field of tourism. It was concluded that the most widespread in the tourist complex are such direct means of state regulation as state registration, accreditation, licensing, provision of other documents of a permissive nature, technical regulation (certification and standardization), sanctions, legislative regulation of tourist activity and its external environment, creation and arrangement of special tourist zones and direct financing of development of tourist infrastructure facilities.
Keywords: tourism; tourist complex; state regulation; development; region; state policy; tools; means